Effects of high-intensity interval exercise on arterial stiffness in individuals at risk for cardiovascular disease: a meta-analysis - Luo, Ping; Wu, Ruoshan; Gao, Weifeng; Yan, Weiyi; Wang, Ruixue; Ye, Yufang (Frontiers in Cardiovascular Medicine, 2024)
Objective: The purpose of this meta-analysis was to investigate the effect of high-intensity interval training (HIIT) on arterial stiffness (AS) and vascular function in persons at high risk of cardiovascular disease (CVD).We conducted a comprehensive search of randomized controlled trials (RCTs) published in electronic databases (PubMed, Web of Science, Cochrane, Embase, and Ebsco) since their inception through October 2023 to evaluate the effect of HIIT on AS and vascular function in persons at high risk for CVD. The weighted mean difference (WMD) and 95% confidence intervals (95% CI) were calculated, and heterogeneity was assessed using the I 2 test.Results: This study included 661 participants from 16 studies. HIIT significantly reduced pulse wave velocity (PWV) in persons at high risk for CVD [weighted mean difference (WMD), -0.62; 95% CI, -0.86 to -0.38; P<0.00001]. Subgroup analysis showed that the PWV improvement effect was better when the HIIT program was performed 2-3 times per week and the duration was controlled within 40 min [2-3 times, -0.67; 95% CI, -0.93 to -0.41; P<0.00001; time of duration, ≤ 40 min, -0.66; 95% CI, -0.91 to -0.41; P<0.00001]. HIIT significantly reduced systolic blood pressure (SBP, -5.43; 95% CI, -8.82 to -2.04; P = 0.002), diastolic blood pressure (DPB, -2.96; 95% CI, -4.88 to -1.04; P = 0.002), and resting heart rate (RHR, -4.35; 95% CI, -7.04 to -1.66; P = 0.002), but had no significant effect on augmentation index (AIX, -2.14; 95% CI, -6.77 to 2.50; P = 0.37).HIIT can improve PWV in high-risk individuals with CVD and reduce SBP, DBP, and RHR, but has no significant effect on AIX. HIIT can effectively improve AS and vascular function and can be recommended as an effective method to improve AS in high-risk persons with CVD.